Otitis media causes and management - Aljohani, Ziyad; Alghonaim, Abdulaziz; Alhaddad, Rayhanah; ALShaif, Wadiah; AlThomali, Rahaf; Asiry, Ali; Hefni, Lujain; Nagadi, Sarah; Taha, Roba (International Journal Of Community Medicine And Public Health, 2018)
Otitis media is a major cause of health care visits across the world, and its complications are significant causes of preventable hearing loss, predominantly in the developing world. They are a group of inflammatory and complex infective conditions that affect the middle ear. They have several different subtypes, and affects primarily children from 3 to 7 years of age. When not treated properly, they can lead to many complications including permanent hearing loss. In this article we will discuss updates on recent scientific developments in the field of otitis media clinical management and research. We conducted this review using a comprehensive search of MEDLINE, PubMed and EMBASE from January 1979 to March 2017. The following search terms were used: otitis media, middle ear infections, pediatric infections, causes of otitis media, treatment otitis media, and prevention of otitis media. Otitis media is one of the most common pathologies in the pediatric age group making it one the most common reasons of doctor visits. Fortunately, the management is simple and promising, but if neglected, can lead to several complications including permanent hearing loss. Newer studies are focusing on preventive measures such as pneumococcal vaccine, and in avoiding creation of resistant species of the common bacteria that cause the pathology.